FAST FASHION; PERILAKU KONSUMSI BERLEBIH - Farah Khumaerah Arif, Nurul; Ambo Masse, Rahman; Sirajuddin, Sirajuddin (Program Studi Ekonomi Syariah, 2024)
The aim of this research is to empirically test students' behavior in consuming excessive fast fashion and find out solutions that students can use to reduce excessive consumption of fast fashion. The method used in this research is a qualitative method using a phenomenological research approach. The data source used is primary data, namely data obtained directly from the original source through interviews. Data analysis carried out by researchers is data collection, data reduction, data presentation, drawing conclusions and verification. The results of this research show that UIN Alauddin Makassar students consume fast fashion in terms of leisure class theory and Monzer Kahf's theory in accordance with the factors that influence them in carrying out this consumption behavior, namely social class, appearance support, personality and self-concept, desires and needs, There are several factors that influence fashionconsumption, namely income, taste, technology, product quality, religion, product price information,attractive product promotions. Meanwhile, according to informants, the negative impacts caused by excessive consumption behavior include reduced savings, increased debt and social jealousy. The conclusion of this research is that excessive behavior is influenced by fomo attitudes and not being able to adapt to current developments